1971
DOI: 10.1149/1.2408351
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conduction in Calcium Doped Polycrystalline Lithium Iodide

Abstract: The ionic conductivity of polycrystalline lithium iodide containing 0 to 3% (mole) calcium iodide was studied at temperatures between −30° and 130°C.The conductivity increased linearly with the concentration of calcium iodide, and it was concluded that the introduction of calcium ions to the lithium iodide crystals induced Schottky defects. The activation energy for the ionic conduction process of 9.96 normalkcal/normalmole agreed well with the value obtained by other investigators. The electronic conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
2

Year Published

1972
1972
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 0 publications
1
18
1
2
Order By: Relevance
“…This cell has an open-circuit voltage of 2.8 V. The theoretical specific energy for the Li/LiI/I 2 (PVP) cell is 1.9 Wh cm -3. The electrolyte ionic conductivity is~6.5 Â 10 À7 S cm À1 at 25 C, and the energy density is 100-200 Wh kg À1 [50]. The ratio of iodine to PVP is typically between 30/1 and 50/1, depending on the manufacturer.…”
Section: Lithium-iodine Cellsmentioning
confidence: 99%
“…This cell has an open-circuit voltage of 2.8 V. The theoretical specific energy for the Li/LiI/I 2 (PVP) cell is 1.9 Wh cm -3. The electrolyte ionic conductivity is~6.5 Â 10 À7 S cm À1 at 25 C, and the energy density is 100-200 Wh kg À1 [50]. The ratio of iodine to PVP is typically between 30/1 and 50/1, depending on the manufacturer.…”
Section: Lithium-iodine Cellsmentioning
confidence: 99%
“…However it should be borne in mind that these results were obtained immediately after quenching the melt containing LiI and the dope. As the authors pointed out, measurements taken after stabilization, at 28~ showed that, for a dope concentration higher than 0.4 mol~, the conductivity remained constant and independent of the initial CaI 2 added [11 ]. This was explained by the authors on the basis that the equilibrium solubility of CaI2 in LiI at 28~ is less than0.4 molto.…”
Section: Thin Film and Doped Electrolyte Cellsmentioning
confidence: 93%
“…This was explained by the authors on the basis that the equilibrium solubility of CaI2 in LiI at 28~ is less than0.4 molto. (1) * As calculated from the reported cell polarization curve [11 ].…”
Section: Thin Film and Doped Electrolyte Cellsmentioning
confidence: 99%
“…The only compound known so far is olivinetype LiEZnI4, which displays fairly high ionic conductivity [ 1,2 ]. No compounds have been obtained in the systems LiI-MgI2 [3,4], LiI-CaI2 [4], LiICdI2 and LiI-HgI2 [ 5 ]. In analogy to the recently established ternary bromides LiEMgBr4 [6,7], LizMnBr4 [6,8,9 ], and LiECdBr4 [ 8 ], the existence of the corresponding iodides was expected.…”
Section: Introductionmentioning
confidence: 99%